The Role of Market Orientation, Creativity and Innovation in Creating Competitive Advantages and Creative Industry Performance - Sutapa, Sutapa; Mulyana, Mulana; Wasitowati, Wasitowati (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
The purpose of this study is to examine the effect of market orientation, creativity, innovation and competitive advantage on the performance of creative industries. Respondents from this study are 130 owners or leaders of creative industries in the fashion sector in Central Java Indonesia. The study is located on the North Coast of Central Java, taking five districts, namely Pekalongan, Semarang, Kudus, Rembang and Jepara. Sampling method in this research use purposive sampling method. This method is used taking into account the criteria of the creative fashion industry that has been operating for at least 3 years and innovating market-oriented products. The data obtained will be analyzed using Partial Least Square (PLS) program. The results of data analysis show that creativity has no significant effect on innovation. Market orientation significantly affects innovation and performance. Innovation also has a significant effect on excellence and competitive performance. Furthermore, competitive advantage has a significant effect on company performance.